OPTIMIZING THE ROLE OF DIGITAL DA'WAH IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION IN INDONESIA - Syamsuri, Syamsuri (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
Digital da'wah has become an important instrument in improving the quality of Islamic education in Indonesia, especially in the era of rapidly developing information technology. This research aims to explore how digital da'wah can be optimized to support Islamic education. With a literature research approach, information is collected from various relevant literature sources and critically analyzed. The results show that digital da'wah can expand access to education, improve interaction between educators and learners, and disseminate information quickly and effectively. In addition, the use of social media and other digital platforms has been proven to attract young people to learn more about Islam. This research emphasizes the importance of integrating digital da'wah in the Islamic education curriculum and the need for further innovation to understand its long-term impact. Thus, optimizing digital da'wah can not only improve the quality of Islamic education but also support the active role of the community in understanding and practicing Islamic teachings